Assessing trait‐based scaling theory in tropical forests spanning a broad temperature gradient. Issue 12 (12th October 2017) - Enquist, Brian J.; Bentley, Lisa Patrick; Shenkin, Alexander; Maitner, Brian; Savage, Van; Michaletz, Sean; Blonder, Benjamin; Buzzard, Vanessa; Espinoza, Tatiana Erika Boza; Farfan‐Rios, William; Doughty, Christopher E.; Goldsmith, Gregory R.; et al.
Abstract: Aim: Tropical elevation gradients are natural laboratories to assess how changing climate can influence tropical forests. However, there is a need for theory and integrated data collection to scale from traits to ecosystems. We assess predictions of a novel trait‐based scaling theory, including whether observed shifts in forest traits across a broad tropical temperature gradient are consistent with local phenotypic optima and adaptive compensation for temperature. Location: An elevation gradient spanning 3, 300 m and consisting of thousands of tropical tree trait measures taken from 16 1‐ha tropical forest plots in southern Perú, where gross and net primary productivity (GPP and NPP) were measured. Time period: April to November 2013. Major taxa studied: Plants; tropical trees. Methods: We developed theory to scale from traits to communities and ecosystems and tested several predictions. We assessed the covariation between climate, traits, biomass and GPP and NPP. We measured multiple traits linked to variation in tree growth and assessed their frequency distributions within and across the elevation gradient. We paired these trait measures across individuals within 16 forests with simultaneous measures of ecosystem net and gross primary productivity. Results: Consistent with theory, variation in forest NPP and GPP primarily scaled with forest biomass, but the secondary effect of temperature on productivity was much less than expected. This weak temperature dependence appears to reflect directional shifts in several mean community traits that underlie tree growth with decreases in site temperature. Main conclusions: The observed shift in traits of trees that dominate in more cold environments is consistent with an 'adaptive/acclimatory' compensation for the kinetic effects of temperature on leaf photosynthesis and tree growth. Forest trait distributions across the gradient showed overly peaked and skewed distributions, consistent with the importance of local filtering of optimal growth traits and recent shifts in species composition and dominance attributable to warming from climate change. Trait‐based scaling theory provides a basis to predict how shifts in climate have and will influence the trait composition and ecosystem functioning of tropical forests.